Foundations of Thought: The Role of Western Philosophy in Shaping Modern Educational Practices - อุทาพันธ์, ภัทรชัย (Journal of Exploration in Interdisciplinary Methodologies (JEIM), 2024)
This paper explores the foundational role of Western philosophy in shaping modern educational practices and its continued relevance in contemporary education. It examines key philosophical ideas from ancient thinkers like Socrates, Plato, and Aristotle, to Enlightenment figures such as John Locke and Jean-Jacques Rousseau, and modern philosophers like John Dewey and Paulo Freire. The paper highlights how these ideas have influenced educational methodologies, including inquiry-based learning, constructivism, and critical pedagogy. Additionally, it addresses the challenges of integrating Western philosophy in diverse educational contexts and balancing tradition with innovation in the face of modern educational demands. The conclusion emphasizes the enduring importance of philosophical thought in fostering critical, reflective, and engaged learners in an increasingly complex world.